Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Characterization of kerogen and bitumen in Type II-S organic-rich chalk as a function of maturity using 2D NMR relaxation - Yunke Liu; Xinglin Wang; George J. Hirasaki; Eva G. Vinegar; Harold J. Vinegar; Philip M. Singer (Fuel, 2024)

Separation of solid and liquid components in organic-rich chalks using NMR relaxation - Yunke Liu; Xinglin Wang; George J. Hirasaki; Eva G. Vinegar; Harold J. Vinegar; Philip M. Singer (Fuel, 2023)

Improvements in brain and behavior following eradication of hepatitis C - Taylor Kuhn; Philip Sayegh; Jacob D. Jones; Jason Smith; Manoj K. Sarma; A. Ragin; Elyse J. Singer; M. Albert Thomas; April D. Thames; Steven A. Castellon; Charles H. Hinkin (Journal of NeuroVirology, 2017)

Strategies for Enhancing the Effectiveness of Metagenomic-based Enzyme Discovery in Lignocellulolytic Microbial Communities - Kristen M. DeAngelis; John M. Gladden; Martin Allgaier; Patrik D’haeseleer; Julian L. Fortney; Amitha Reddy; Philip Hugenholtz; Steven W. Singer; Jean S. Vander Gheynst; Whendee L. Silver; Blake A. Simmons; Terry C. Hazen (BioEnergy Research, 2010)

Characterization of Single-Phase Flow Through Carbonate Rocks: Quantitative Comparison of NMR Flow Propagator Measurements with a Realistic Pore Network Model - Weishu Zhao; Guillemette Picard; Gabriela Leu; Philip M. Singer (Transport in Porous Media, 2010)